PASCAL, Blas (2020). Escritos espirituales. Edición de Alicia Villar. Madrid: Tecnos. - Gómez Sánchez, Carlos (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: PASCAL, Blas (2020). Escritos espirituales. Edición de Alicia Villar. Madrid: Tecnos.